2009
DOI: 10.1093/ndt/gfp588
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel kappa-receptor agonist, nalfurafine hydrochloride, on severe itch in 337 haemodialysis patients: a Phase III, randomized, double-blind, placebo-controlled study

Abstract: This Phase III, randomized, double-blind, placebo-controlled, parallel-group, prospective study based on VAS evaluations clearly showed that orally taken nalfurafine hydrochloride effectively reduced itches that were otherwise refractory to currently available treatments in maintenance haemodialysis patients, with few significant ADRs. This novel drug was officially approved for clinical use in January 2009 by the Ministry of Health, Labour and Welfare of Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
222
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(239 citation statements)
references
References 24 publications
9
222
1
7
Order By: Relevance
“…It may have a direct effect on the brain and/or provide positive feedback from the skin at the level of the spinal cord. Its effect on itching in randomized trials was less than gabapentin, and its most common side effect is insomnia (14). There remains a need for a more robust evidence base for these and other agents, such as turmeric, montelukast, zinc sulfate, and nalbuphine (15)(16)(17)36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may have a direct effect on the brain and/or provide positive feedback from the skin at the level of the spinal cord. Its effect on itching in randomized trials was less than gabapentin, and its most common side effect is insomnia (14). There remains a need for a more robust evidence base for these and other agents, such as turmeric, montelukast, zinc sulfate, and nalbuphine (15)(16)(17)36).…”
Section: Discussionmentioning
confidence: 99%
“…Nalfurafine, a k-opioid receptor agonist, reduced the severity of itch by 0.95 cm more than placebo on a 10-cm visual analog scale score in one randomized, controlled trial (13) and by 0.9 and 1.0 cm more than placebo in a second using two doses (14). Single randomized, controlled trials of turmeric, montelukast, and zinc sulfate have shown a significant reduction in itch compared with placebo and warrant further study (15)(16)(17).…”
Section: Introductionmentioning
confidence: 98%
“…Currently, the mechanism underlying morphine-related pruritus remains uncertain, but morphine-induced pruritus is considered mediated by the l-opioid receptors 31 and the j-opioid receptors. 32,33 Accordingly, administration of butorphanol (a partial l-opioid receptor antagonist and j-opioid receptor agonist) with morphine (l-and j-receptor agonist) would be expected to maintain analgesia (l-and j-receptors) while reducing pruritus. 21 Butorphanol has been used to treat intractable pruritus based on its potential anti-pruritus effect, 5 but debate on the efficacy of prophylactic butorphanol on morphine-induced pruritus still exists.…”
Section: Discussionmentioning
confidence: 99%
“…Wikström et al (2005) and Kumagai et al (2010) reported the results of randomized, doubleblind, placebo-controlled clinical studies in which TRK-820 was administered to patients undergoing hemodialysis intravenously or orally (Fig. 5).…”
Section: Clinical Studiesmentioning
confidence: 99%